Intracranial Carotid Artery Calcification Relates to Recanalization and Clinical Outcome After Mechanical Thrombectomy. Issue 2 (February 2017) - Hernández-Pérez, María; Bos, Daniel; Dorado, Laura; Pellikaan, Karlijn; Vernooij, Meike W.; López-Cancio, Elena; Pérez de la Ossa, Natalia; Gomis, Meritxell; Castaño, Carlos; Munuera, Josep; Puig, Josep; Millán, Mònica; et al.
Abstract : Background and Purpose—: Intracranial carotid artery calcification (ICAC) is a surrogate marker of intracranial arteriosclerosis, which may impact the revascularization and clinical outcome of acute stroke patients who undergo mechanical thrombectomy. Methods—: We included 194 patients admitted to our Stroke Unit between January 2009 and September 2015 who underwent mechanical thrombectomy for an anterior circulation occlusion. ICAC was quantified in both intracranial carotid arteries on the nonenhanced computed tomographic scan that was acquired before thrombectomy. Complete arterial revascularization was defined as a Thrombolysis in Cerebral Infarction ≥2b on the final angiographic examination. Poor functional outcome was defined as a modified Rankin Scale score of >2 at 90 days. We assessed the independent effect of ICAC volume on complete arterial revascularization, functional outcome, and mortality using logistic regression models adjusted for relevant confounders. Results—: ICAC was present in 164 (84.5%) patients, with a median volume of 87.1 mm 3 (25th–75th quartile: 18.9–254.6 mm 3 ). We found that larger ICAC volumes were associated with incomplete arterial revascularization (adjusted odds ratio per unit increase in ln-transformed ICAC volume 0.73 [95% confidence interval, 0.57–0.93]) and with poorer functional outcome (adjusted odds ratio per unit increase in ln-transformed ICAC volume 1.31 [95% confidence interval, 1.04–1.66]). Conclusions—: A larger amount of ICAC before mechanical thrombectomy in acute stroke patients is an indicator of worse postprocedural arterial revascularization and poorer functional outcome. Abstract : Supplemental Digital Content is available in the text.